The Influence Of Manual System Port Services To Inapornet On Users Of Belawan Port Services At PT. Adhigana Pratama Mulya Belawan - Putra Sanjaya Sianturi; Syarifur Ridho; Lilis Lilis; Fadiyah Hani Sabila (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to find out the port service process and what obstacles occur during the port service process. There are several obstacles experienced by service users in ship service activities via Inaportnet. The first is that PNBP payments (VTS, signs and dangerous goods) are still manual, the reason being that service users don't understand Inaportnet. Apart from that, updates to computer devices. When using Inaportnet, system errors often occur. Efforts that can be made are to carry out updates so that PNBP payments can also be made online, carry out training and socialization about Inaportnet filling, update computer equipment and evaluate and upgrade the Inaportnet application.